The MotionMonitor (2011)
Real-time 3D motion capture system designed for use in medical research; physical therapy clinics; sports medicine labs; motor control & neurological labs; gait & balance labs; golf, tennis & baseball instruction centers and, other situations where precise measurements of the body and its movement through time are required. The most advanced data acquisition, analysis and visualization system in the market place, The MotionMonitor® is configured to meet specific requirements. It is characterized by: synchronized data collection from Ascension "Flock of Birds" & trakStar; Polhemus Liberty & Patriot; Motion Analysis Corp, Qualisys & Vicon passive optical systems; Optotrak Certus, Phoenix & PhaseSpace active optical systems; Organic Motion markerless cameras; AMTI, Bertec & Kistler force plates, Delsys & Noraxon EMG; BioSemi EEG; SR Research Eyelink II and Eyelink 1000; Phantom haptic devices; SenseGraphics stereoscopic displays, and digital video; rich data analysis, stunning 3D computer renderings, and an underlying foundation in science.